Parental willingness to have children vaccinated against COVID-19 in Geneva, Switzerland: a cross-sectional population-based study (Swiss Medical Weekly, 2023)
OBJECTIVE: We aimed to examine factors associated with parental willingness to vaccinate their children against COVID-19.METHODS: We surveyed adults included in a digital longitudinal cohort study composed of participants in previous SARS-CoV-2 serosurveys conducted in Geneva, Switzerland. In February 2022, an online questionnaire collected information on COVID-19 vaccination acceptance, parental willingness to vaccinate their children aged ≥5 years and reasons for vaccination preference. We used multivariable logistic regression to assess the demographic, socioeconomic and health-related factors associated with being vaccinated and with parental intention to vaccinate their children.RESULTS: We included 1,383 participants (56.8% women; 69.3% aged 35–49 years). Parental willingness to vaccinate their children increased markedly with the child’s age: 84.0%, 60.9% and 21.2%, respectively, for parents of adolescents aged 16–17 years, 12–15 years and 5–12 years. For all child age groups, unvaccinated parents more frequently indicated not intending to vaccinate their children than vaccinated parents. Refusal to vaccine children was associated with having a secondary education (1.73; 1.18–2.47) relative to a tertiary education and with middle (1.75; 1.18–2.60) and low (1.96; 1.20–3.22) household income relative to high income. Refusal to vaccine their children was also associated with only having children aged 12–15 years (3.08; 1.61–5.91), aged 5–11 years (19.77; 10.27–38.05), or in multiple age groups (6.05; 3.22–11.37), relative to only having children aged 16–17 years.CONCLUSION: Willingness to vaccinate children was high for parents of adolescents aged 16–17 years but decreased significantly with decreasing child age. Unvaccinated, socioeconomically disadvantaged parents and those with younger children were less likely to be willing to vaccinate their children. These results are important for vaccination programs and developing communication strategies to reach vaccine-hesitant groups, both in the context of COVID-19 and in the prevention of other diseases and future pandemics.